A Latent Class Analysis on Symptoms of Prolonged Grief, Post-Traumatic Stress, and Depression Following the Loss of a Loved One - Heeke, Carina; Franzen, Minita; Hofmann, Hendrik; Knaevelsrud, Christine; Lenferink, Lonneke I. M. (Frontiers in Psychiatry, 2022)
The loss of a significant other can lead to variety of responses, including prolonged grief disorder (PGD), posttraumatic stress disorder (PTSD), and depression. The aim of this study was to replicate and extend previous research that indicated that three subgroups of bereaved individuals can be distinguished based one similar post-loss symptom profiles using latent class analysis (LCA). The second aim was to examine whether sociodemographic and loss-related characteristics as well as the extent of meaning making were related to classes with more pervasive psychopathology. Telephone-based interviews with 433 Dutch and German speaking persons who had lost a significant other at last six months earlier were conducted. Self-rated PGD, PTSD, and depression symptoms were assessed. LCA was conducted and correlates of class-membership were examined using the 3step approach. The LCA resulted in three distinct classes: a no symptoms class (47%), a moderate PGD, low depression/ PTSD class (32%), and a high PGD, moderate depression/ PTSD class (21%). A multivariate analysis indicated that female gender, a shorter time since loss, an unexpected loss and less meaning made to a loss were significantly associated with membership to the moderate PGD, low depression/ PTSD and high PGD, moderate depression/ PTSD class compared to membership to the no symptom class. Losing a child or spouse, a shorter time since loss, and having made less meaning to the loss further distinguished between the high PGD, moderate depression/ PTSD symptom class and the moderate PGD, low depression/ PTSD class. We found that the majority of individuals coped well in response to their loss since the no symptom class was largest class. Post-loss symptoms could be categorized into classes marked by different intensity of symptoms, rather than qualitatively different symptom patterns. The findings indicate that perceiving the loss as more unexpected, finding less meaning in the loss, and loss-related factors, such as the recentness of a loss and the loss of a partner or child, were related to class membership more consistently than sociodemographic factors.